PERCEPTION OF PORT SERVICE USERS ON QUALITY OF PORT OFFICE SERVICE (UPP) GARONGKONG KABUPATEN BARRU - Safaruddin; Muhammad Anwar (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal